The Technology Education System Staffing: Problems and Solutions - D. P. Danilaev; N. N. Malivanov (Высшее образование в России)
The strategic objective of modern technological education is to prepare children for life in a high-tech competitive world. The implementation of this task encounters the problems of material and technical equipment of educational institutions and their staffing. An integrated approach based on the pooling of all resources and efforts of interested parties is needed to organize a technological education modern system. Training programs for teachers should take into account their interdisciplinary nature, and include the psychological, pedagogical, and natural-science components, so as technical aspects. The important segment of technology education is training of technical specialists without pedagogical background to work at schools and universities, as well as training of school teachers and university lectures based on the modern technological order. In this regard, a new look at the IGIP programs is possible, these program goals and objectives interpretation should be applied to the teacher training within the system of high-school technological education.The article considers the approaches to solving the problems of high-school technological education system staffing, presents the comparative analysis of the current educational programs. The experience in training technical university teachers, masters of industrial instruction, technology teachers should be adjusted in accordance with the global changes in science, technique and technology.